2022
DOI: 10.3389/fonc.2022.924409
|View full text |Cite
|
Sign up to set email alerts
|

Use of long non-coding RNAs for the molecular diagnosis of papillary thyroid cancer

Abstract: ObjectiveImproved molecular testing for common somatic mutations and the identification of mRNA and microRNA expression classifiers are promising approaches for the diagnosis of thyroid nodules. However, there is a need to improve the diagnostic accuracy of such tests for identifying thyroid cancer. Recent findings have revealed a crucial role of long non-coding RNAs (lncRNAs) in gene modulation. Thus, we aimed to evaluate the diagnostic value of selected lncRNAs from The Atlas of Noncoding RNAs in Cancer (TAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Generally, combining several biomarkers can increase the accuracy of diagnosis. For example, Kim et al found that the combination of LRRC52-AS1, LINC02082, and UNC5B-AS1 lncRNAs accurately diagnose PTC [ 131 ]. To improve the diagnostic accuracy of PTC more conveniently and increase its clinical utility, Wu et al identified seven downregulated circulating lncRNAs (TCONS_00516390, TCONS_00336559, TCONS_00311568, TCONS_00321917, TCONS_00336522, TCONS_00282483, and TCONS_00494326) with the ability to predict the occurrence of PTC [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, combining several biomarkers can increase the accuracy of diagnosis. For example, Kim et al found that the combination of LRRC52-AS1, LINC02082, and UNC5B-AS1 lncRNAs accurately diagnose PTC [ 131 ]. To improve the diagnostic accuracy of PTC more conveniently and increase its clinical utility, Wu et al identified seven downregulated circulating lncRNAs (TCONS_00516390, TCONS_00336559, TCONS_00311568, TCONS_00321917, TCONS_00336522, TCONS_00282483, and TCONS_00494326) with the ability to predict the occurrence of PTC [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, 8 Cuproptosis-connected lncRNAs (IRAG1-AS1 AF064860.2 AC233266.2 LINC01063 AC084781.2 LINC01518 UNC5B-AS1 AL050404.1) were detected via LASSO regression and multivariate Cox regression analysis. In the lncRNAs model connected to Cuproptosis, UNC5B-AS1was an elevated risk factor for the osteosarcoma prognosis in Cuproptosis-related lncRNAs [31], which enhanced the liver cancer cells' migration, growth, and epithelial interstitial transformation [32], and was highly expressed in papillary thyroid carcinoma [33],LINC01063 was an oncogene in melanoma [34] and it was autophagyassocitaed lncRNA to anticipate the Colorectal tumor prognosis [35],About LINC01518, it was shown to be an endogenous RNA that competes in oesophageal squamous cell cancer [36]. So far, there has been no detailed investigation on the remaining ve lncRNAs connected to Cuproptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, we detected eight cuproptosis-related lncRNAs (IRAG1-AS1, AF064860.2, AC233266.2, LINC01063, AC084781.2, LINC01518, UNC5B-AS1, and AL050404.1) via LASSO regression and multivariate Cox regression analysis. In the lncRNA model related to cuproptosis, UNC5B-AS1 was found to be a risk factor for poor osteosarcoma prognosis (Yang et al 2022), which enhanced liver cancer cell migration, growth, and epithelial interstitial transformation (Huang et al 2021) and was highly expressed in papillary thyroid carcinoma (Kim et al 2022). Moreover, LINC01063 was identi ed as an oncogene in melanoma (Xu et al 2022) and an autophagy-associated lncRNA that could predict the prognosis of colorectal tumor (Duan et al 2022), whereas LINC01518 was shown to be an endogenous RNA that competes in esophageal squamous cell cancer (Zhang et al 2019).…”
Section: Discussionmentioning
confidence: 99%